2011
DOI: 10.2217/fca.10.191
|View full text |Cite
|
Sign up to set email alerts
|

ABO Blood Groups and Thrombosis: A Causal association, But is There Value in screening?

Abstract: ABO(H) antigens are expressed on red cells and on von Willebrand factor. An association between groups other than O and thrombosis exists: an effect that is predominantly mediated by von Willebrand factor. Overall, the risk of venous thrombosis associated with non-O has been estimated at 1.75-fold, with a higher risk (∼ 2.4-fold) in those with the least O(H) antigen (a combined group of A(1)A(1)/A(1)B/BB). Preliminary evidence also suggests that blood group may influence the venous thromboembolism risk associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 86 publications
1
24
0
Order By: Relevance
“…The products resulting from the complex interaction of the ABO(H), Lewis and Secretor genes are displayed on red cells and other cell types and as free substances in body secretions. There is convincing evidence that ABO(H) blood groups are associated with thrombotic risk, resulting, in part, from higher levels of von Willebrand factor (VWF) in those with blood groups other than O [2,3]. A role for Lewis/Secretor status in thrombosis has also been reported, but is more controversial [4][5][6][7][8][9][10], as is the link between Lewis or Secretor and VWF levels [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The products resulting from the complex interaction of the ABO(H), Lewis and Secretor genes are displayed on red cells and other cell types and as free substances in body secretions. There is convincing evidence that ABO(H) blood groups are associated with thrombotic risk, resulting, in part, from higher levels of von Willebrand factor (VWF) in those with blood groups other than O [2,3]. A role for Lewis/Secretor status in thrombosis has also been reported, but is more controversial [4][5][6][7][8][9][10], as is the link between Lewis or Secretor and VWF levels [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the association between ABO blood groups and DVT were different. Some studies have showed that non-O blood groups were associated with higher incidence DVT than blood group O,5-8 while in Wolpin’s study the hazard ratios for DVT were similar in non-O group 11. In pregnancy and the puerperium, there is also more high risk for DVT in blood groups A and AB than in blood group O 12.…”
Section: Discussionmentioning
confidence: 89%
“…Some studies have addressed the potential role of ABO blood groups in DVT. Compared with blood group O, non-O blood groups have higher risk for DVT 5-8. However, the association between ABO blood groups and DVT vary significantly among geographic region and race.…”
mentioning
confidence: 97%
“…Additionally, blood group A and B are known to be highly susceptible to thrombotic disorders in contrast to group O individuals who are more at risk for bleeding than thrombotic events [3234]. This observation has been attributed to higher levels of Factor VIII and von Willebrand factor in A and B individuals, while the levels may be as low as 30% in group O individuals.…”
Section: Blood Group Disease Associationsmentioning
confidence: 99%